2007
DOI: 10.1159/000108414
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Human Immunodeficiency Virus Type 1 Activity by Purified Human Breast Milk Mucin (MUC1) in an Inhibition Assay

Abstract: It has been reported that breast-feeding is responsible for approximately 40% of the HIV transmissions from HIV-positive mothers to children. Human breast milk, however, is known to contain numerous biologically active components which protect breast-fed infants against bacteria, viruses, and toxins. The purpose of this study was to purify and characterize breast milk mucin and to determine its anti-HIV-1 activity in an HIV inhibition assay. Sepharose CL-4B column chromatography and caesium chloride isopycnic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
41
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 56 publications
(44 reference statements)
6
41
0
Order By: Relevance
“…The tolerance of VSV to MUC1 is a significant result. Although the role of MUC1 in oncolytic therapy has never been studied before, the O-linked carbohydrates of MUC1 purified from human breast milk can inhibit poxvirus (12), HIV (13,14), and rotavirus (15), and MUC1 expression can block adeno-associated virus attachment (16). Although VSV-⌬M51-GFP was slightly less infectious in MUC1-expressing KCM cells than in MUC1-null KCKO cells, the opposite could be seen in Panc02-based cell lines ( Fig.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The tolerance of VSV to MUC1 is a significant result. Although the role of MUC1 in oncolytic therapy has never been studied before, the O-linked carbohydrates of MUC1 purified from human breast milk can inhibit poxvirus (12), HIV (13,14), and rotavirus (15), and MUC1 expression can block adeno-associated virus attachment (16). Although VSV-⌬M51-GFP was slightly less infectious in MUC1-expressing KCM cells than in MUC1-null KCKO cells, the opposite could be seen in Panc02-based cell lines ( Fig.…”
Section: Discussionmentioning
confidence: 96%
“…MUC1 plays an important role in the development and progression of PDA and other cancers and is a major marker for poor prognosis (7)(8)(9)(10)(11). Importantly, while the role of MUC1 in vesicular stomatitis virus (VSV) infection or oncolytic virus (OV) therapy has never been studied before, the O-linked carbohydrates of MUC1 purified from human breast milk can inhibit poxvirus (12), HIV (13,14), and rotavirus (15), and MUC1 expression can block adeno-associated virus attachment (16).…”
mentioning
confidence: 99%
“…We also showed that crude virus-free breast milk did not inhibit the virus, while purified mucin did [12]. …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it was recently established that milk of uninfected women abrogates oral HIV-1 transmission in humanized mice (10). Several antiviral glycoproteins contained in milk have been reported to inhibit HIV-1 replication, including lactoferrin (11,12), mucin-1 (13), and secretory leukocyte protease inhibitor (14,15). In addition, a recent study reported an association between the prevalence of certain oligosaccharides in milk and the risk of infant HIV-1 acquisition (16), potentially explained by the ability of oligosaccharides to prevent HIV-1 virion interaction with dendritic cells (17,18).…”
mentioning
confidence: 99%